Protection: challenges to the United Nations High Commission for Refugee and Malaysia’s government - Kunapalan, Hemamalani; Ismail, Norafidah; Yatiban, Aminurraasyid (2016)
Refugee or asylum seekers are more than simply a human rights issue.Refugee movements are also an essential part of international politics.This study will delve into the Malaysian government and United Nations High Commission for Refugees (UNHCR) challenges for the protection of refugee in Malaysia.The UNHCR operation in Malaysia is not without problems.Even though Malaysia is not a signatory to the 1951 Convention Relating to the Status of Refugees and its 1967 Protocol, that does not mean that nothing can be done to protect the refugees in the country.The reasons Malaysia should cooperate with UNHCR needs to be addressed rapidly to find a long term solution for this problem.This will then followed by analyzing Malaysia’s international commitment and obligation relating to Refugee in general .Discussion will touch on the role of Malaysia as a state party to the United Nation(UN) and it’s refusal to ratify the 1951 Convention Relating to the Status of Refugee (CRSR).Other dimension of this paper is the highlight of the mechanism that Malaysia’s government should adapt to assist the UNHCR in resolving the challenges. Finding of this study will show the extent of protection offered to refugees under domestic laws and the reasons why Malaysia should fulfill its international obligation towards refugee and also the further effort that must be initiated to clinch compliance to protection under international law.